Zika, dengue, and chikungunya co-infection in a pregnant woman from Colombia (2016)
The clinical findings of a pregnant woman from Colombia with a triple co-infection caused by dengue, chikungunya, and Zika viruses are described. Weekly obstetric ultrasounds from 14.6 to 29 weeks of gestation were normal. She remains under follow-up and management according to the standard guidelines for the management of Zika virus-infected pregnant women.